Project-level Women’s Empowerment in Agriculture Index for Market Inclusion (Pro-WEAI+MI): Philippines Case Study - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
The project-level Women’s Empowerment in Agriculture Index for market inclusion (pro-WEAI+MI) is a modified version of the pro-WEAI that captures empowerment across commodity value chains (VC), VC actors, and beneficiaries of VC/training interventions. This dataset from the Philippines is the first of four country case studies that developed additional market inclusion (+MI) indicators to complement the pro-WEAI.